Hubungan Tingkat Pengetahuan Dan Perilaku Ibu Terhadap Pelaksanaan Deteksi Dini Kanker Serviks Di Puskesmas Panei Tongah Kecamatan Panei Tongah Kab Simalungun Tahun 2021 - Hutagalung, Mei Linda; Sembiring, Isyos Sari; Damayanty; Vernandasari, Yenni; Sianipar, Angel Thesalonica Marito; Nainggolan, Dwi Vivi (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2021)
According to WHO data, cancer is the leading cause of death in the world. In Indonesia, based on Basic Health Research data, the prevalence of tumor/cancer in Indonesia is 1.4 per 1000 population. According to the American Cancer Society (2016), cervical cancer mortality rates have fallen by more than 50% over the past 30 years. The main reason for this change is the increased use of the Pap Smear test. The purpose of this study was to determine the relationship between the level of knowledge and mother's behavior on the implementation of early detection of cervical cancer at the Panei Tongah Health Center, Panei District, Simalungun Regency in 2021. This type of research is an analytic observational study, namely research that seeks the relationship between one variable and another. The design of this study used a cross sectional approach, namely a study that was conducted with only one observation and measurements were made on the status of the character or variable of the subject at the time of the study. The population in this study were 95 respondents. The results showed that from 95 people there was a p value of 0.001 < 0.05. This means that there is a relationship between knowledge and the implementation of early detection of cancer. Implementation of early detection of cancer, with the number of behaviors supporting the implementation of the Pap smear as an early detection of cervical cancer is the p value is 0.001 <0.05. The results of statistical tests found that there was a relationship between knowledge on the implementation of early cancer detection with a p value of 0.001 < 0.05, and there was a significant relationship between behavior towards the implementation of early cancer detection with a p value of 0.001 < 0.05.